Branderpreneurship Framing Analysis of LALULA in Developing Business and Brand Values - Roby Zul Fanani; Ersal Bioldy; Andy Lasuardy; Forestya Sartika (Graduate School of Communication Universitas Bakrie, 2025)
The growth of startups and micro, small, and medium enterprises (MSMEs) in Indonesia has given birth to local children's fashion business brands that can compete closely with the desires of the mother segment, who want their children to look fashionable, quality, and up-to-date. This study analyzes how LALULA, a local children's fashion brand, builds and implements brand value using Qualitative Branderpreneurship Framing Analysis (QI.BFA). The study delves into the brand's strategic efforts from the seven elements of the Branderpreneurship's Circle of Values ​​Development (BrandCoVD) framework, showcasing the innovative strategies and frameworks implemented by LALULA to build and implement its brand value. Data were collected through in-depth interviews with various parties who work as employees at LALULA and analysis of related documents. The study results show that LALULA focuses on product value through product innovation, creative marketing, and building close customer relationships. These findings provide valuable insights for practitioners and academics about the importance of Branderpreneurship in developing sustainable brand value, equipping them with practical knowledge for their own brand development endeavors.